Transnational Social Implications of the Use of the “War metaphor" Concerning Coronavirus: A Birds' Eye View - Emilia Martinez-Brawley; Estrella Gualda (Culture e Studi del Sociale)
This paper reflects on the force of the war metaphor primarily in Spain and the U.S. Examples from other countries are included. Methodologically, it utilizes the literature (journals and newspapers) and Twitter research. The paper addresses the impact and pervasiveness of English language translations in electronic communications. A bird’s eye view of how the war metaphor spread during the pandemic is presented. Additionally, the paper discusses idiosyncratic differences, cultures and histories in an Anglo-Saxon country and a Latin one. The topic of how leaders in different countries used the war metaphor to regulate the activities of citizens and manage their own political realities is reviewed. The situation of immigrants during the pandemic is discussed. The paper includes manifestations of those differences in celebrations, and mourning relating to the pandemic. Recommendations for future research on the war metaphor and its effects on solidarity and the economy of nations are put forward.